Contribuições de um programa educacional de introdução à linguagem cartográfica tátil para alunos com cegueira - Giehl, Fabiana Cristina (2015)
Based on the understanding that the appropriate use of tactile maps facilitates the interpretation of space and its use for students with visual impairment, this study emphasizes the importance of educational programs towards the reading and interpretation of a map. This study aimed to analyze the contributions of an educational program to introduce the tactile cartographic language to students with visual impairment. In order to perform this research it has carried out a descriptive investigation outlined by a multi case study. The participants of this research were two teachers who assist on Specialized Educational Service (AEE), two teachers from regular school and two students with visual impairment with different ages (seven and ten years old). The research it has developed with the application of the following tools: semi structured interview; questionnaire and pedagogical evaluation. All data were registered in diaries, filming and photography. The content of interviews, pedagogical evaluation and diary were submitted to the theory of content analysis. The educational program has contributed to improve the ability of students with visual impairment to identify the tactile cartographic variable used in maps. In this context, it is suggested that the Tactile Cartography make part of the curriculum of graduation in Geography, Pedagogy and all related graduation courses in order to prepare teachers to work with students with visual impairment.